2015
DOI: 10.1108/bfj-09-2013-0276
|View full text |Cite
|
Sign up to set email alerts
|

External sources for innovation in food SMEs

Abstract: Purpose - The purpose of this paper is to examine the role that different external sources of knowledge play in product, process, market and organizational innovations in food SMEs. Design/methodology/approach - This study is based on a web-survey of 214 food European SMEs. Binary logistic regression models were utilized for data analysis. Findings - The findings support the recent studies that suggest that the introduction of different types of innovation is associated with different types of source of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 81 publications
3
61
0
10
Order By: Relevance
“…This study addresses a gap pointed out in literary literature by Alfiero, et al (2017), Farsi & Toghraee (2014), Greeven & van de Kaa (2013), Lefebvre et al (2015) and Zhang, Groen & Belousova (2018) when investigating innovation-related issues in small low-tech food enterprises, analyzing the case of Food Trucks in an emerging country as representatives of street entrepreneurs. While current studies understand that, due to their low technological standards, street entrepreneurs are not innovative (Reynolds et al, 2002;Bhola et al, 2006), the results of this investigation indicate differently.…”
Section: Main Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…This study addresses a gap pointed out in literary literature by Alfiero, et al (2017), Farsi & Toghraee (2014), Greeven & van de Kaa (2013), Lefebvre et al (2015) and Zhang, Groen & Belousova (2018) when investigating innovation-related issues in small low-tech food enterprises, analyzing the case of Food Trucks in an emerging country as representatives of street entrepreneurs. While current studies understand that, due to their low technological standards, street entrepreneurs are not innovative (Reynolds et al, 2002;Bhola et al, 2006), the results of this investigation indicate differently.…”
Section: Main Findingsmentioning
confidence: 95%
“…However, the understanding of how entrepreneurs in emerging market enhance innovation performance is still limited (Zhang, Chen & Kane, 2018). In fact, despite the maturity of food sector, there are still relatively few studies regarding innovationrelated issues (Lefebvre et al, 2015). Most of the existent researches focus on high-tech industries (Vrontis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Same four categories of innovations were used in a study of sources of information supporting innovations in food industry (Lefebvre, De Steur, & Gellynck, 2015) and focuses on the types of knowledge associated with various types of innovations. The authors reported several studies where companies introduced innovations in the food industry (product, process and marketing or all four categories).…”
Section: Categories Of Innovationmentioning
confidence: 99%
“…Currently, the limited “absorptive capacity” of SMEs (Saguy and Sirotinskaya ) is the main obstacle in university‐industry collaboration. SMEs being guided by markets perceive research organizations as irrelevant (Lefebvre and others ). A fundamental shift from defensive market‐orientated strategies toward offensive market‐developing is needed.…”
Section: Operational Approachesmentioning
confidence: 99%